TAHAPAN J.BRUNER DALAM PEMBELAJARAN MATEMATIKA PADA PENJUMLAHAN DAN PENGURANGAN BILANGAN BULAT DI SEKOLAH DASAR (SD/MI) - Widyaningrum, Retno (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2011)
Teaching is not only changing ones behavior but more importantly it function to change the school curriculum on such a way that students can learn easily and optimally. It is essential to take an action to improve the studentsâ ability in math based on their own nature development, particularly in primary schools level. This can be gained by creating the students active participation and regarding their diversity of as conveyed by J. Bruner. In order to improve the quality of learning process, it is necessary to set up a convenience environment known as "discovery learning environment" that is an environment where learners can explore, invent new knowledge, or discover similar to those already known. There are three stages of learning according to J. Bruner, such as enactive, iconic and symbolic stages. The learning process will be gained optimally if the students are involved in enactive stage, and then if this phase of learning is well-achieved, students learn to switch to the second stage by employing the iconic representation mode. Lastly, learning activities are preceded to the third stage, which is the learning phase by using the mode of symbolic representation. By implementation those three learning objectives, it is expected that the process of learning mathematics can achieve the intended goals.ÙÙØ³ Ø§ÙÙØ¯Ù ÙÙ Ø§ÙØªØ¹ÙÙÙ Ø§ÙØªØºÙÙØ± ÙÙ Ø³ÙÙÙ Ø§ÙØ·Ø§ÙØ¨ ÙØØ³Ø¨. Ø¨Ù Ø§ÙØªØºÙÙØ± ÙÙ Ø§ÙÙÙÙØ¬ Ø§ÙØ¯Ø±Ø§Ø³Ù ÙØ°ÙÙØ ÙÙØ°Ø§ ÙÙØ¯Ø±Ø³ Ø§ÙØ·Ø§ÙØ¨ Ø£ÙØ«Ø± ÙØ£Ø³ÙÙ. Ø§ÙÙØØ§ÙÙØ§Øª ÙØªÙÙÙØ± Ø§ÙÙØ±Øµ ÙÙØ·ÙØ§Ø¨ ÙÙØªÙØ¯ÙÙØ§ Ø³Ø±ÙØ¹Ø§ ÙÙÙØ§ Ø¨ÙØ¯Ø±Ø§ØªÙ ÙÙ Ø§ÙÙØ§Ø¯Ø© Ø§ÙØ®Ø§ØµØ© ( Ø®Ø§ØµØ© ÙÙ Ø§ÙÙØ±ØÙØ© Ø§ÙØ§Ø¨ØªØ¯Ø§Ø¦ÙØ©) Ø ÙØ°Ø§ Ø¨Ø§ÙØ§ÙØªÙØ§Ù ÙØÙ Ø§Ø´ØªØ±Ø§ÙÙÙ ÙÙ Ø§ÙØªØ¹ÙÙÙ ÙØ§ÙØªØ¹Ø±Ù Ø¹ÙÙ Ø®ØµØ§Ø¦Øµ Ø§ÙØ·ÙØ§Ø¨ ÙÙØ§ ÙÙÙÙÙ Ø¬ Ø¨Ø±ÙÙØ±. ÙÙØªØ±ÙÙØ© Ø¹ÙÙÙØ© Ø§ÙØªØ¹ÙÙÙ ÙØØªØ§Ø¬ Ø§ÙÙØ¯Ø±Ø³ Ø¥ÙÙ Ø¨ÙØ¦Ø© (Discovery learning environment ( ÙÙÙ Ø§ÙØ¨ÙØ¦Ø© Ø§ÙØªÙ Ø¨ÙØ§ ÙØ³ØªØ·ÙØ¹ Ø§ÙØ·Ø§ÙØ¨ ØªÙØ³ÙØ¹ ÙØ¹ÙÙÙØ§ØªÙ ÙØ§ÙÙØ¯Ø±Ø© Ø¹ÙÙ Ø§ÙØ§Ø¨Ø¯Ø§Ø¹Ø§Øª Ø£Ù Ø§ÙÙÙØ§ÙÙÙ Ø§ÙÙØ³Ø§ÙÙØ© ÙÙØ§ ÙÙ ÙØ¹ÙÙÙ ÙÙÙ. ÙØ¨Ø§ÙÙØ¸Ø± Ø¥ÙÙ Ø£Ù Ø«ÙØ© 3 ÙØ±Ø§ØÙ ÙÙ Ø§ÙØªØ¹ÙÙÙ ÙÙØ§ Ø°ÙØ±Ù Ø¬ Ø¨Ø±ÙÙØ± ÙÙ Ø¥ÙÙÙØªÙÙ Ù Ø¥ÙÙÙÙÙ Ù Ø³ÙÙØ¨ÙÙÙ Ø ÙØ¹ÙÙÙØ© Ø§ÙØªØ¹ÙÙÙ Ø³ÙÙØ¬Ø Ø¥Ø°Ø§ Ø¨Ø¯Ø¦ Ø¨ÙØ±ØÙØ© Ø¥ÙÙÙÙÙÙ Ø«ÙÙ Ø§ÙÙØ±ØÙØ© Ø§ÙØ«Ø§ÙÙØ© ÙÙÙØ°Ø§. ÙØªØ·Ø¨ÙÙ ÙØ°Ù Ø§ÙÙØ±Ø§ØÙ ÙÙ Ø§ÙØ¹ÙÙÙØ© Ø§ÙØªØ¹ÙÙÙÙØ© Ø®Ø§ØµØ© ÙØ§Ø¯Ø© Ø§ÙØ±ÙØ§Ø¶ÙØ§Øª ÙØ±Ø¬Ù ÙÙÙ Ø§ÙØØµÙÙ Ø¹ÙÙ Ø§ÙØ£ÙØ¯Ø§Ù ÙÙ Ø§ÙØªØ¹ÙÙÙ.